Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Comparative stable isotope analyses of green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) in the San Francisco estuary - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Molly Webb; A. Peter Klimley (Journal of Fish Biology, 2024)
Green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) are closely related, sympatric species that inhabit the San Francisco estuary. Green sturgeon have a more marine life history but both species spawn in the Sacramento River and reside for some duration in San Francisco Bay. These sturgeons are of conservation concern, yet little is known about their dietary competition when they overlap in space and time. To examine evidence of dietary differentiation, we collected whole blood and blood plasma from 26 green sturgeon and 35 white sturgeon in San Francisco Bay. Using carbon and nitrogen stable isotope analyses, we compared their relative trophic levels and foraging locations along the freshwater to marine gradient. Sampling blood plasma and whole blood allowed comparison of dietary integration over shorter and longer time scales, respectively. Plasma and whole blood δ 13 C values confirmed green sturgeon had more marine dietary sources than white sturgeon. Plasma δ 15 N values revealed white sturgeon fed at lower trophic levels than green sturgeon recently, however, whole blood δ 15 N values demonstrated the two species fed at the same trophic level over longer time scales. Larger individuals of both species had higher δ 13 C values than smaller individuals, reflecting more marine food sources in adulthood. Length did not affect δ 15 N values of either species. Isotope analyses supported the more marine life history of green than white sturgeon and potentially highlight a temporary trophic differentiation of diet between species during and preceding the overlapping life stage in San Francisco Bay.

Movement patterns of juvenile green sturgeon (Acipenser medirostris) in the San Francisco Bay Estuary - Michael J. Thomas; Andrew L. Rypel; Gabriel P. Singer; A. Peter Klimley; Matthew D. Pagel; Eric D. Chapman; Nann A. Fangue (Environmental Biology of Fishes, 2022)
Little is known about the distribution and ecology of juvenile green sturgeon throughout their range and specifically within California’s Central Valley and the San Francisco Bay Estuary. The objective of our study was to identify rearing movement patterns of juvenile green sturgeon and their interaction with Delta and Bay habitats. Acoustic biotelemetry was used to record juvenile movements and residence within different regions of this highly modified watershed. We document a diversity of movements exhibited by 31 acoustically tagged juvenile green sturgeon monitored over a 9-month period. The juvenile sturgeon either (1) remained in the Delta or moved (2) into the Carquinez Straits, (3) into San Pablo Bay, (4) into San Pablo Bay but returned to Delta, (5) through the estuary and likely left through the mouth of the bay, (6) or left the estuary only to return later. Spatiotemporal habitat quality varies within and between Delta and Bay habitats. Variation in water year and hydrologic connectivity are likely to influence habitat quality and quantity, and behaviors may be differentially optimized for fitness in response to environmental variation. Our results provide initial evidence supporting multiple behavioral movement patterns and a broad use of regional habitats for green sturgeon in the California Central Valley. This apparent behavioral diversity observed through movement patterns may ensure long-term success of all population segments over time in an extremely variable environment, ultimately supporting overall population stability (i.e., the portfolio effect). Enhanced conservation efforts may be needed to protect juvenile green sturgeon and the habitats they rely upon.

Correction to: Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Historic drought influences outmigration dynamics of juvenile fall and spring-run Chinook Salmon - Gabriel P Singer; Eric D. Chapman; Arnold J. Ammann; A. Peter Klimley; Andrew L. Rypel; Nann A. Fangue (Environmental Biology of Fishes, 2020)

Spatiotemporal occurrence of green sturgeon at dredging and placement sites in the San Francisco estuary - Eric D. Chapman; Emily A. Miller; Gabriel P. Singer; Alex R. Hearn; Michael J. Thomas; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2019)

Flagship umbrella species needed for the conservation of overlooked aquatic biodiversity - Gregor Kalinkat; Juliano S. Cabral; William Darwall; G. Francesco Ficetola; Judith L. Fisher; Darren P. Giling; Marie‐Pierre Gosselin; Hans‐Peter Grossart; Sonja C. Jähnig; Jonathan M. Jeschke; Klaus Knopf; Stefano Larsen; et al. (Conservation Biology, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Movements of steelhead (Oncorhynchus mykiss) smolts migrating through the San Francisco Bay Estuary - Eric D Chapman; Alex R Hearn; Gabriel P Singer; William N Brostoff; Peter E LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2015)

Movements of out-migrating late-fall run Chinook salmon (Oncorhynchus tshawytscha) smolts through the San Francisco Bay Estuary - Alex R. Hearn; Eric D. Chapman; Gabriel P. Singer; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Behavior, movements, and habitat use of adult green sturgeon, Acipenser medirostris, in the upper Sacramento River - Michael J. Thomas; Matthew L. Peterson; Eric D. Chapman; Alex R. Hearn; Gabriel P. Singer; Ryan D. Battleson; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Interannual variation of reach specific migratory success for Sacramento River hatchery yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) - Gabriel P. Singer; Alex R. Hearn; Eric D. Chapman; Matthew L. Peterson; Peter E. LaCivita; William N. Brostoff; Allison Bremner; A. P. Klimley (Environmental Biology of Fishes, 2013)

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Diel movements of out-migrating Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) smolts in the Sacramento/San Joaquin watershed - Eric D. Chapman; Alex R. Hearn; Cyril J. Michel; Arnold J. Ammann; Steven T. Lindley; Michael J. Thomas; Philip T. Sandstrom; Gabriel P. Singer; Matthew L. Peterson; R. Bruce MacFarlane; A. Peter Klimley (Environmental Biology of Fishes, 2013)